A Project Report on Characteristics Studies on Dairy Waste Water of Bangalore Dairy - HANUMANTHAPPA, KORIRAGHAVENDRA, PRADEEP K M and SANTOSH KUMAR (2012)
INTERNAL GUIDE: Dr ASHA K, MVJCE
Keywords: Characteristics Studies on Dairy Waste Water of Bangalore Dairy